Monitoring and assessing the species diversity and abundance of marine teleost around the Yellow River estuary in June using environmental DNA - Lyu, Ding; Qian, Tangyi; Li, Fan; Sun, Song; Wang, Weiji; Shan, Xiujuan (Frontiers in Marine Science, 2023)
The Yellow River estuary is an important feeding, reproduction and development ground of variety of marine economic species. Understanding the species composition and abundance changes around the Yellow River estuary was of great significance. In this study, trawl survey and seawater eDNA survey were carried out simultaneously around the Yellow River estuary with the objective of both understanding the composition of marine teleost around the Yellow River estuary and providing a reference for the application of eDNA to the fishery resources survey. The results showed 31 species of marine teleost in all were detected using trawl survey, and 33 species were detected using eDNA technology. The number of species detected by both methods was 21. In these 21 species, the Pearson's correlation coefficients between their eDNA relative abundance and catch per unit effort (CPUE) were very high (0.993 for weight and 0.993 for quantity), while the spearman correlation coefficients were 0.659 and 0.595, respectively. There were significant positive correlations between biomass of specific species and their eDNA relative abundance. Species composition difference analysis based on eDNA showed that the species compositions of two low salinity and low water depth survey stations were distinctly different from the others. This study not only scientifically monitored and evaluated species diversity and abundance of teleost around the Yellow River estuary, but also provided a reference for the application of eDNA to the fishery resources survey.